Efficacy of MSC-derived small extracellular vesicles in treating type II diabetic cutaneous wounds: a systematic review and meta-analysis of animal models - Yue, Guangren; Li, Yu; Liu, Zheng; Yu, Shuying; Cao, Yilin; Wang, Ximei (Frontiers in Endocrinology, 2024)
Background: Small extracellular vesicles derived from mesenchymal stem cells (MSC-sEVs) have emerged as a promising therapy for treating type II diabetic cutaneous wounds. Currently, the evidence supporting the use of MSC-sEVs for treating diabetic skin wounds remains inconclusive and is limited to preclinical studies. To facilitate the clinical translation of cell-free therapy, conducting a comprehensive systematic review of preclinical studies assessing the efficacy of MSC-sEVs is imperative.A systematic search was conducted on PubMed, Web of Science, Embase, and Cochrane Library databases until June 14, 2023, to identify studies that met our pre-established inclusion criteria. The outcome indicators comprised wound closure rate (primary outcome), neovascular density, re-epithelialization rate, collagen deposition, and inflammatory factors (secondary Outcomes). A fixed-effects model was employed in instances of low heterogeneity (I 2 <50%), while a random-effects model was utilized for high heterogeneity (I 2 ≥50%). The risk of bias in animal studies was assessed using the SYRCLE tool.Results: Twenty-one studies were included in this meta-analysis. Compared with the control group, MSC-sEVs were found to significantly facilitate the healing of cutaneous wounds in type II diabetic patients (standardized mean difference [SMD]=3.16, 95% confidence interval [CI]: 2.65 to 3.66, P<0.00001, I 2 =39%).According to the meta-analysis of preclinical studies, MSC-sEVs show promising applications in promoting type II diabetic wound healing. As a result, translating these findings into clinical applications appears warranted.